CÜVEYNÎ’NİN “EL-AKİDETÜ’N-NİZAMİYYE” ADLI ESERİNE ÇAĞDAŞ BİR TA’LÎK ÖRNEĞİ - Ramazan Altıntaş (İslami İlimler Dergisi)
In this article is stated about an exposition (Ta’lik) about “Akidetun’n Nizamiyye” which written by Cuveyni. This Ta’lik (exposition) is belong to Dr. Ahmed Hicazi. It is very important for to advance the Islamic theology (Kalam) tradition. Because if we don’t know our tradition, we won’t construct our future. As is known, the Tal’iks are very important and useful to understand the traditional texts. The Dr. Ahmed Hicazi’ tal’ik (exposition) is the one of the best example. Author who is a Mutezile is to make criticism the Cuveyni’ book who is an Eş’ari. There are a lot of examples about his criticisms. Therefore I think the study of Dr. es-Sakka, is answered How a modern Tal’ik will be?